“It Makes you Want to Go Out and Change the World”: Shifts in Victim Advocates’ Perspectives Following the Intimate Partner Homicide of a Client in the United States - AbiNader, Millan A. (Journal of family violence, 2024)
Purpose: Intimate partner violence (IPV) victim advocates are exposed daily to the traumas of their clients, including the potential exposure to an intimate partner homicide (IPH). While research has examined the effects of daily secondary exposure to IPV on victim advocates, little is known about the specific effect of IPH. This study examined how the IPH of a client affected advocates’ perception of and approach to their work. Methods: Nine advocates were recruited from the northeastern U.S. and interviewed about their experience of the IPH of a client. Advocate interviews were analyzed using The Listening Guide Analysis which systematically isolates and listens to the different, and often contradictory, voices that a participant uses. Results: Exposure to IPH changed participants’ perception of their role, how they defined client, and how they interacted with future clients. At a macro-level, the IPH of a client motivated advocates to advance changes in agency protocol, multisector responses, and state policy based on what they had learned from the IPH. Opportunities to translate shifts in their worldview into tangible changes to protocol and policy were critical to advocate adjustment after the IPH. Conclusions: In order to support advocates after IPH, organizations should acknowledge the potentially transformative effect of IPH and create opportunities for meaning making to assist in advocate adjustment. It is imperative for advocacy organizations to support their employees to prevent advocate burnout and the loss of experienced staff, and to continue to provide effective services to vulnerable members of their communities after IPH.